2023
DOI: 10.7759/cureus.34723
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bariatric Surgery on Cardiovascular Outcomes and Cardiovascular Mortality: A Systematic Review and Meta-Analysis

Abstract: Obesity is a major public health problem that is associated with serious comorbidities and premature mortality. Cardiovascular disease (CVD) is the major cause of morbidity and mortality associated with obesity. Lifestyle modifications, pharmacological therapy, and weight reduction surgery are the major interventions to date available for obesity management. Bariatric surgery has been increasingly utilized as a therapeutic option for obesity. In this meta-analysis, we aim to assess the effects of bariatric sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 77 publications
0
2
0
1
Order By: Relevance
“…Numerous studies have demonstrated that MBS is significantly more effective than dietary and lifestyle changes alone at inducing weight loss, reducing complications, comorbidities, and mortality, and improving patients’ overall quality of life [ 6 , 8 , 10 , 11 , 22 24 ]. Such reductions in complications and comorbidities include improvements in existing conditions and their prevention, including the prevention of various cardiometabolic diseases and cancers demonstrated also in multiple meta-analyses [ 25 34 ]. But questions persist as to when MBS might be contraindicated and which procedure to select in different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that MBS is significantly more effective than dietary and lifestyle changes alone at inducing weight loss, reducing complications, comorbidities, and mortality, and improving patients’ overall quality of life [ 6 , 8 , 10 , 11 , 22 24 ]. Such reductions in complications and comorbidities include improvements in existing conditions and their prevention, including the prevention of various cardiometabolic diseases and cancers demonstrated also in multiple meta-analyses [ 25 34 ]. But questions persist as to when MBS might be contraindicated and which procedure to select in different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Esta reducción se debe sobre todo a una reducción en la mortalidad de causa CV y por cáncer 40 . La cirugía bariátrica, mediante sleeve gástrico, bypass en Y de Roux o banda gástrica, ha demostrado una menor incidencia en la ECV, el IM, la IC, el ACV, la FA, la mortalidad de causa CV y la mortalidad por todas las causas 40 , 41 . Además, estudios recientes demuestran una mejoría modesta en el remodelado cardíaco tras la cirugía bariátrica 42 .…”
Section: Efecto De La Pérdida De Peso Sobre La Enfermedad Cardiovascu...unclassified
“…La cirugía metabólica es el tratamiento quirúrgico de reducción de peso que además busca corregir una comorbilidad, como la diabetes o la hipertensión arterial. Es el único tratamiento con evidencia científica que ha demostrado ser eficaz a corto, mediano y largo plazo para lograr, no solamente una importante disminución de peso, sino también una reducción del riesgo cardiovascular global y la mortalidad total [20][21][22] . Si bien hay literatura que menciona que también mejora la calidad de vida, las autoras tenemos ciertas dudas al respecto, por lo menos en relación a que esta mejoría sea 'absoluta', ya que los pacientes pueden pasar de una condición (obesidad con otros factores de riesgo cardiovascular) a otra que describiremos más adelante.…”
Section: ¿En Qué Consiste La Cirugía Metabólica?unclassified